Digital literacy in the multimedia age: the culture after the digital - Barroso, Paulo (2020)
In the 1960s, McLuhan warned early on that the trend of mass societies to become a “global village” due to the development and impact of new technological means of information and communication. Today, the effects of the media are gradually being felt, as technology dominates the daily uses of the media and the social practices of communication and information and, therefore, requires a constant requalification of literacy, which is as diverse the media themselves. Therefore, it is pertinent to understand the renewed demands of literacy and the technological effects of the media on audiences. Based on McLuhan’s theses on the mass media and their technological effects, a critical strategy and a theoretical-conceptual approach are followed. The objective is to problematize and discuss the role of digital media and its effects on literacy. Do mass societies and cultures, resulting from the profound transformations of globalization, make citizens more informed, enlightened, literate, demanding and committed to the “common good”? Do we communicate more and better in the current golden age of technology and digital communication? Is there media literacy for audiences to discern what is true and what is false in the content transmitted by the media?